2021
DOI: 10.3390/ijerph19010428
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Key Factors Related to the Decision of a Do-Not-Resuscitate Consent

Abstract: Background: The decision to sign a do-not-resuscitate (DNR) consent is critical for patients concerned about their end-of-life medical care. Taiwan’s National Health Insurance Administration (NHIA) introduced a family palliative care consultation fee to encourage family palliative care consultations; since its implementation, identifying which families require such consultations has become more important. In this study, the Taiwanese version of the Palliative Care Screening Tool (TW–PCST) was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Notably, most patients’ DNR orders had been signed by their spouses or families when the patients were unconscious or unable to express their wishes clearly and independently after ICU admission [ 23 ]. However, many patients’ families have difficulty making DNR decisions for their loved ones, and choose to continue life-sustaining treatment to prolong their life [ 5 ], but patients who receive a family palliative care consultation are more likely to sign a DNR consent [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, most patients’ DNR orders had been signed by their spouses or families when the patients were unconscious or unable to express their wishes clearly and independently after ICU admission [ 23 ]. However, many patients’ families have difficulty making DNR decisions for their loved ones, and choose to continue life-sustaining treatment to prolong their life [ 5 ], but patients who receive a family palliative care consultation are more likely to sign a DNR consent [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the medical professionals did not give up any chances for prolonging the patient’s survival [ 34 ]. The DNR order appears beneficial in limiting futile cardiac resuscitation practices to ensure terminally ill patients a peaceful natural death [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Taiwan National Health Insurance Administration 2012 provided family PC consultation fees to encourage family consultations, allowing inpatients to effectively access PC services through conference among the medical team, patient, and family members. This provides an opportunity to receive PC at their end of life, thereby enhancing the quality of good death in these patients [22][23][24][25][26]. The WHO suggested that PC services should be activated while lengthening life to provide a holistic perspective [27].…”
Section: Of 12mentioning
confidence: 99%
“…Within 24 h of a patient’s admission, nursing staff of Taipei City Hospital use the patient’s Palliative Care Screening Tool-Taiwan version (TW-PCST) score to identify whether family palliative care consultation is required. The TW-PCST evaluates four categories: (1) the severity of the baseline disease process; (2) the severity of the comorbidity process; (3) functional performance status; and (4) whether the patient has had frequent admissions or intensive care unit (ICU) stays [ 9 ].…”
Section: Introductionmentioning
confidence: 99%